Pengaruh Permainan Tradisional Gedrek Terhadap Kemampuan Numerasi Anak Kelompok B - Azizah Hi. Taher; Icam Sutisna; Apriyanto A.J Pauweni (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
This study aims to determine the influence of the traditional game “Gedrek” on children’s numeracy abilities. This research is quantitative experimental research (one group pretest-posttest design). Based on the study findings with a total sample of 15, which was divided into 8 boys and 7 girls, children showed an increase in the average pre-test results with an average value of 14.6, while the post-test result obtained an average result of 21.6. These results demonstrated that there is a significant effect before and after the treatment. Based on the t-test results at (α)=0.05, ttable = 2.131 and obtained tcount value = 10.913. Thus, tcount ≥ table, 10.913 ≥ 2.131, in other words, tcount > ttable, Then Ho is rejected, and Hi is accepted, thus the hypothesis is accepted. This showed there is an influence of the Gedrek Traditional Game on the Numerical Ability of Group B Children in TK State 12 Kartini Kindergarten, Wonosari District, Boalemo Regency.